Herstories. Digital social archives as a space for building memory about women (presentation of the research area) - Ciesek-Ślizowska, Bernadetta (Stylistyka, 2019)
The aim of the article is to shape the field of scientific exploration which is opening in the internet space as a social archive. It is a space for building herstories – women’s histories as well as social memory about them. The author refers to the definition of herstory by presenting a variety of contexts in which the concept functions: ideological, scientific, and that which is created by bottom-up initiatives of social archival science. Herstoric discourse, being shaped in the space of digital social archives, fits into the intense and changing public discourse on equality. A discursive overview of herstory will enhance our knowledge not only of equality/ anti-discriminative discourse regulations, but also about civil or urban discourse. What is more, it will provide new findings on the topic of women’s style and point of view. There are also valuable social effects of discursive interest in herstories – they can contribute to including women’s histories, their voices and way of thinking about the world into the public sphere.